Varian Paradigmatis dan Pengaruh Teori Kritis Dalam llmu Komunikasi - Erry, hadiati (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2007)
Science communication in ifs early years start from science positivism.Science communication paradigm is also start from a positive empiric methodoly matters. Shannon-Weaver mechanistic approach states that communication is mechanic pieces human do which basically imitating transmitter and receiver machines.Communicationis a linear mechanisticprocess that comes from derivation of nature science in human behaviour cluster. Some of basic models in science communication is a matter of full distention belween researcher and researchee. obiectivity-rnechanistic, deductive-nomologic and factual external research from eve,y symptom in human communicativebehaviour. -Positivism in science communication form a social science that has authoritarianand negative characteristic, except for rules and system that required corelational fest. This paper give brief picture an alternative approach for communicationscience.Thereare several arguments in public which cannot be explained only by numbers and percentage. Numbers sometimes create ideological missconcepfion. This articlefriesto develop feorificalapproach in a practicalframework.